Clinical profile of patients with surgical brain abscesses and etiology in a reference hospital - Calderón-Garcidueñas, Ana Laura; Gayón-Lombardo, Erika; Salazar-Félix, Alejandro; Rocandio-Hernández, Daniel; Tena-Suck, Martha Lilia; Sánchez-Garibay, Carlos (The Journal of Infection in Developing Countries, 2024)
Introduction: The annual incidence of brain abscesses is 1–2% in developed countries and up to 8% in developing countries. Our aim was to describe the profile and etiological agents of patients with surgical brain infections according to their nosological diagnosis on admission, and to analyze whether the initial diagnosis influenced the neurological deficit at discharge. Methodology: This was an observational study with convenience sampling. All surgical cases operated between January 2017 and February 2022 with a final diagnosis of an infectious process were included. Three groups were analyzed according to admission diagnosis: a) infection, b) neoplasia, and c) miscellaneous. The time before admission, final histological diagnosis, etiological agent, length of hospital stay, and secondary neurological deficits were investigated. Descriptive and comparative statistics were used. Results: 24 cases, including 18 (75%) men and 6 (25%) women, of ages 19 to 61 years (average 43.7 years) were studied. Nosological diagnoses on admission were infection in 9 (37.5%) patients, cerebral neoplasia in 9 (37.5%) patients, and miscellaneous diagnoses in 6 (25%) patients. Among the miscellaneous, neoplastic, and infectious groups, 33.3%, 33.3%, and 22.2% of patients were discharged with some neurological deficits with overall neurological morbidity and mortality of 29.6% and 8%, respectively. The etiological agents were Mycobacterium tuberculosis (16.6%), Streptococcus sp. (13%), Morganella morganii (8.7%), Nocardia sp. (4.3%), Cryptococcus sp. (4.3%), and Klebsiella sp. (4.3%). Conclusions: Nosological diagnosis on admission did not influence the percentage of patients with neurological deficits in our study. Mycobacterium was the most frequent etiological agent.